Synthesis of Porous Clay Heterostructures Modified with SiO2–ZrO2 Nanoparticles for the Valorization of Furfural in One‐Pot Process. (16th March 2022) - Essih, Salima; Cecilia, Juan Antonio; Jiménez‐Gómez, Carmen Pilar; García‐Sancho, Cristina; García‐Mateos, Francisco José; Rosas, Juana María; Moreno‐Tost, Ramón; Franco, Francisco; Maireles‐Torres, Pedro
Abstract: The layered structure of two smectites (montmorillonite and saponite) are modified by the insertion of SiO2 –ZrO2 nanoparticles, with a Si/Zr molar ratio of 5, to form porous clay heterostructures (PCHs). These PCHs exhibit a clear improvement of the textural and acid properties in comparison to the starting clays, due to the formation of a pillared structure and the presence of Zr species, which provide an increase in the amount of Lewis acid sites. These materials are studied in one‐pot catalytic processes to transform furfural into valuable products, such as furfuryl alcohol, alkyl furfuryl ethers, alkyl levulinates or γ‐valerolactone, depending on the experimental conditions. Thus, the use of milder reaction temperature (110 °C) favors the formation of furfuryl alcohol and alkyl furfuryl ethers, while higher temperatures (170 °C) promote the formation of alkyl levulinate and γ‐valerolactone, as well as an increase in nondetected products associated to the formation of humins due to the polymerization of furfural and/or furfuryl alcohol. Abstract : The insertion of SiO2 –ZrO2 nanoparticles in montmorillonite and saponite clays gives rise to active catalysts for the catalytic transfer hydrogenation of furfural, under consecutive reactions (one‐pot). Mild temperatures favor the formation of furfuryl alcohol and alkyl‐furfuryl ethers, whereas alkyl‐levulinates and γ‐valerolactone are mainly detected at higher temperatures.